Modulating hair follicle size with Wnt10b/DKK1 during hair regeneration. Issue 6 (June 2014) - Lei, Mingxing; Guo, Haiying; Qiu, Weiming; Lai, Xiangdong; Yang, Tian; Widelitz, Randall B.; Chuong, Cheng‐Ming; Lian, Xiaohua; Yang, Li
Abstract Hair follicles have characteristic sizes corresponding to their cycle‐specific stage. However, how the anagen hair follicle specifies its size remains elusive. Here, we showed that in response to prolonged ectopic Wnt10b‐mediated β‐catenin activation, regenerating anagen hair follicles grew larger in size. In particular, the hair bulb, dermal papilla and hair shaft became enlarged, while the formation of different hair types (Guard, Awl, Auchene and Zigzag) was unaffected. Interestingly, we found that the effect of exogenous WNT10b was mainly on Zigzag and less on the other kinds of hairs. We observed dramatically enhanced proliferation within the matrix, DP and hair shaft of the enlarged AdWnt10b‐treated hair follicles compared with those of normal hair follicles at P98. Furthermore, expression of CD34, a specific hair stem cell marker, was increased in its number to the bulge region after AdWnt10b treatment. Ectopic expression of CD34 throughout the ORS region was also observed. Many CD34‐positive hair stem cells were actively proliferating in AdWnt10b‐induced hair follicles. Importantly, subsequent co‐treatment with the Wnt inhibitor, DKK1, reduced hair follicle enlargement and decreased proliferation and ectopic localization of hair stem cells. Moreover, injection of DKK1 during early anagen significantly reduced the width of prospective hairs. Together, these findings strongly suggest that Wnt10b/DKK1 can modulate hair follicle size during hair regeneration.